Capital market instruments : analysis and valuation - Choudhry, Moorad (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2010)
"This is an updated guide to some of the most important issues in the capital markets today. Fundamental concepts in equity market analysis, foreign exchange and money markets are also covered to provide a comprehensive overview. The book includes an accompanying CD-ROM with RATE software, designed to introduce readers to yield curve modelling"--Provided by publisher.
Περιέχει βιβλιογραφία και ευρετήριο.
Keywords: Capital market; Financial instruments; Investment analysis